Aktivitas Antikoagulan dari Tumbuhan Kayu Ular (Strychnos lucida R.Br.) - Elsye Gunawan; Aris A.L. Toruan; Rusnaeni Rusnaeni; Felycitae E. Appa (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
The stem of the snakewood plant (Strychnos lucida) has been used empirically as a malaria drug, relieves fever, treats stomach pain, hemorrhoids, rheumatism, stroke symptoms, and improves blood circulation. Tannins as one of the secondary metabolites of snakewood stems contain gallic acid compounds which are known to thin the blood. The purpose of this study was to determine the anticoagulant activity of the ethanolic extract of snakewood stems on blood group samples, namely A, B, AB, and O. The method used for extraction was maceration, for testing anticoagulants used method modified Lee-White and blood smears, as well as for data analysis carried out descriptively. The results obtained by the Lee-White modification method on blood group samples were visually not clotting. For anticoagulant activity by blood smear method, it was shown that microscopically snakewood bark extract prevented the presence of blood clots which could be observed with unrelated blood cells, intact and separated from each other.Key words: S. lucida; Lee-White modification; blood smear; anticoagulants